2012
DOI: 10.1289/ehp.1103647
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Particle Pollution, Ozone, and Ambient Temperature on Arterial Blood Pressure

Abstract: Background: Diabetes increases the risk of hypertension and orthostatic hypotension and raises the risk of cardiovascular death during heat waves and high pollution episodes.Objective: We examined whether short-term exposures to air pollution (fine particles, ozone) and heat resulted in perturbation of arterial blood pressure (BP) in persons with type 2 diabetes mellitus (T2DM).Methods: We conducted a panel study in 70 subjects with T2DM, measuring BP by automated oscillometric sphygmomanometer and pulse wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
104
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 34 publications
15
104
7
1
Order By: Relevance
“…O 3 concentrations are highly correlated with temperature. Hoffmann et al 28 observed that O 3 and higher temperature were associated with decreases in SBP in a study of the short-term effects of ambient air pollution and temperature on arterial BP in 70 people with type 2 diabetes mellitus. Although the combined effects of these 2 factors are not clear, the effect of O 3 exposure on SBP in the study might be masked by an independent temperature effect on SBP.…”
Section: Discussionmentioning
confidence: 99%
“…O 3 concentrations are highly correlated with temperature. Hoffmann et al 28 observed that O 3 and higher temperature were associated with decreases in SBP in a study of the short-term effects of ambient air pollution and temperature on arterial BP in 70 people with type 2 diabetes mellitus. Although the combined effects of these 2 factors are not clear, the effect of O 3 exposure on SBP in the study might be masked by an independent temperature effect on SBP.…”
Section: Discussionmentioning
confidence: 99%
“…28 Short-term exposures to particle pollution (including black carbon and OC) were associated with increases in blood pressure, whereas increases in O 3 were linked to blood pressure decreases in a repeated measures study of patients with type 2 diabetes mellitus. 18 In elderly subjects with coronary artery disease from the Los Angeles, CA, basin, exposure to primary components of fossil fuel combustion (eg, OC) was associated with ST-segment depression 39 and with elevated ambulatory blood pressure. 40 Associations of OC with higher blood pressure were of greatest magnitude among obese participants.…”
Section: Short-term Exposures/acute Effectsmentioning
confidence: 99%
“…102 Many studies have suggested that people with type 2 diabetes mellitus may be more vulnerable to the acute effects of particles on blood pressure and other vascular responses. 18,103 As discussed in our 2008 review, 102 diabetesassociated chronic inflammation and oxidative stress may quench nitric oxide, create imbalances in vasoactive mediators in arterial tissue, change smooth muscle responsiveness as a result of chronic autonomic dysfunction, or impair flowmediated dilation as a result of vascular remodeling. Animal models support obesity and diabetes mellitus as sources of vulnerability to cardiovascular effects of particle mass: Exposure to PM 2.5 increased the risk of insulin resistance in rats fed a high-fat diet but not in those fed a normal-chow diet.…”
Section: Preexisting Chronic Conditions: Diabetes Mellitus and Obesitymentioning
confidence: 99%
See 2 more Smart Citations